2019
DOI: 10.1101/724997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Cytogenetics Reveals Molecular Stoichiometry and Longitudinal Organization of Meiotic Chromosome Axes and Loops

Abstract: During meiosis, chromosomes adopt a specialized organization involving assembly of a cohesin-based axis along their lengths, with DNA loops emanating from this axis. We applied novel, quantitative and widely applicable cytogenetic strategies to elucidate the molecular bases of this organization using C. elegans. Analyses of WT chromosomes and de novo circular mini-chromosomes revealed that meiosis-specific HORMA-domain proteins assemble into cohorts in defined numbers and co-organize the axis together with two… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…We also found a slight (approximately 1.2 times increase, n=6 gonads) but significant increase of panHIM-3 intensity on short arms after partitioning, suggesting a net addition of HIM-3 proteins to the SC toward the end of pachytene ( Figure 3B ). This is consistent with the previous observation that HIM-3 and HTP-1/2 continue to accumulate on the SC throughout pachytene and diplotene [33] . In nuclei with partitioned HIM-3phos, panHIM-3 staining levels did not differ between short and long arms, suggesting that the chromosome-wide increase in panHIM-3 levels does not derive from preferential addition of HIM-3 proteins to short arms but rather global addition along the entire SC ( Figure 3C ).…”
Section: Phosphorylated Him-3 Localizes To the Entire Length Of The Ssupporting
confidence: 93%
See 2 more Smart Citations
“…We also found a slight (approximately 1.2 times increase, n=6 gonads) but significant increase of panHIM-3 intensity on short arms after partitioning, suggesting a net addition of HIM-3 proteins to the SC toward the end of pachytene ( Figure 3B ). This is consistent with the previous observation that HIM-3 and HTP-1/2 continue to accumulate on the SC throughout pachytene and diplotene [33] . In nuclei with partitioned HIM-3phos, panHIM-3 staining levels did not differ between short and long arms, suggesting that the chromosome-wide increase in panHIM-3 levels does not derive from preferential addition of HIM-3 proteins to short arms but rather global addition along the entire SC ( Figure 3C ).…”
Section: Phosphorylated Him-3 Localizes To the Entire Length Of The Ssupporting
confidence: 93%
“…A previous study has shown that HTP-1/2 is able to bind either to HIM-3 or HTP-3's closure motifs [24] . A more recent study has shown that on average two HTP-1/2 molecules and three HIM-3 molecules are present at every HTP-3 molecule, with substantial variation between HTP-3 molecules [33] . This indicates that closure motifs are rarely if ever occupied to their theoretical maximum; instead, many must remain unbound.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The existence of cohesin oligomers is consistent with the in vitro detection of mammalian cohesin dimers, the co-immunoprecipitation of differentially tagged cohesins isolated from mammalian cells, and functional cooperation between mutated yeast cohesins in vivo (Eng et al, 2015;Kim et al, 2019;Srinivasan et al, 2018;Zhang et al, 2008) . A recent in vivo imaging study of worms suggests that clusters (~4) of cohesins containing COH-3/COH-4 bind at distinct loci on meiotic chromosomes (Woglar et al, 2020) . These clusters and the proximity of the head and hinges of COH-3/COH-4 cohesins is also consistent with the oligomerization of cohesins in the butterfly conformation (Köhler et al, 2017;Woglar et al, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo imaging study of worms suggests that clusters (~4) of cohesins containing COH-3/COH-4 bind at distinct loci on meiotic chromosomes (Woglar et al, 2020) . These clusters and the proximity of the head and hinges of COH-3/COH-4 cohesins is also consistent with the oligomerization of cohesins in the butterfly conformation (Köhler et al, 2017;Woglar et al, 2020) . Thus, oligomers of cohesin butterflies may be conserved in eukaryotes.…”
Section: Discussionmentioning
confidence: 99%